Analisis Hukum Penyelesaian Kerugian Negara Ditinjau Dalam Perspektif Hukum Pidana - Idris, Siswan; Kadir, Yusrianto; Amu, Robby W. (CV. Era Digital Nusantara, 2023)
This study aims to determine and analyze the process and mechanism for resolving State Financial Losses in the Perspective of Criminal Law and to determine and analyze the application and legal settlement of the findings of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) on the occurrence of state financial losses in state financial management. This research uses library data (library research) to obtain theoretical or doctrinal conceptions, opinions or conceptual thoughts from previous research related to the objects examined in this study which can be in the form of laws and regulations, books, scientific works, papers and other works. The results of the research show that the existence of Article 4 of the PTPK Law as the basis for law enforcement of corruption that harms state finances is to emphasize that when state financial losses have switched or entered the realm of criminal law, the return of financial losses does not eliminate the criminal liability of the perpetrators of corruption that harms state finances and the Supreme Audit Agency Regulation Number 3 of 2007 concerning Procedures for Settling State Losses Against Treasurers starts from handling initial information, which starts with information on state / regional losses then proceeds with the formation of the State Loss Settlement Team (TPKN); then Examination by the Supreme Audit Agency; Settlement through Certificate of Absolute Responsibility (SKTJM); Settlement through Decision Letter of Deadline Determination (SKPBW); and Settlement through Encumbrance Decision Letter (SKP).